2003
DOI: 10.1351/pac200375091197
|View full text |Cite
|
Sign up to set email alerts
|

Boron clusters for medicinal drug design: Selective estrogen receptor modulators bearing carborane

Abstract: The molecular shape and hydrophobicity of dicarba-closo -dodecaboranes may allow a new medical application as biologically active molecules. Recently, we have developed potent estrogen receptor (ER) agonists bearing carborane cage. The most potent compound (BE120) exhibited activity at least several times greater than that of 17 beta-estradiol in luciferase reporter gene assay and ER alpha binding. We also designed and synthesized estrogen antagonists on the basis of the structure of BE120, and we noticed the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 0 publications
1
49
0
1
Order By: Relevance
“…These properties suggest the use of carbaboranes as phenyl mimetics and their introduction into bioactive structures by replacement of aromatic rings, making them highly interesting targets for the design of novel drugs. [6,10,12] …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These properties suggest the use of carbaboranes as phenyl mimetics and their introduction into bioactive structures by replacement of aromatic rings, making them highly interesting targets for the design of novel drugs. [6,10,12] …”
Section: Introductionmentioning
confidence: 99%
“…Carbaboranes are icosahedral clusters with ten BH and two CH vertices and a volume slightly larger than that of a rotating benzene ring. [1] Besides their use in catalysis and polymer chemistry, [2] carbaborane derivatives were developed for medicinal applications, primarily for use as boron neutron capture therapy (BNCT) agents; [3][4][5] however, their potency as novel pharmacophores in drug development [1,[6][7][8][9][10][11][12][13][14][15] has also been recognized. [16][17][18] In this context, dicarba-closo-dodecaboranes [closo-C 2 B 10 H 12 ] are regarded as promising candidates given their remarkable metabolic stability and low toxicity as well as their high hydrophobicity and three-dimensional aromaticity.…”
Section: Introductionmentioning
confidence: 99%
“…We have synthesized a range of carboranyl phenol derivatives and have discovered various types of ER modulators, partial agonists, super-agonists, antagonists, and SERMs. [11][12][13][14][15][16][17][18] In addition, our quantitative structure-activity relationship (QSAR) studies of very simple carboranyl phenols showed that the hydrophobicity of the carborane cage is significantly correlated with ERα-binding affinity. 30,31) Although carboraNote * To whom correspondence should be addressed.…”
Section: )mentioning
confidence: 93%
“…1,9,10) Subsequently, many carboranyl phenol derivatives have been synthesized and their estrogen-related biological activities examined. [11][12][13][14][15][16][17][18] Compounds that either induce or inhibit cellular estrogenic responses are used for estrogen replacement therapy after menopause or the treatment of breast cancer, respectively. [19][20][21] Tissue-selective ligands, which act as agonists for bone metabolism and as antagonists for the female reproductive systems (known as selective estrogen receptor modulators, SERMs) are widely used for the treatment of osteoporosis.…”
mentioning
confidence: 99%
“…Indeed, carborane-containing ligands exhibited the enhanced binding affinities to a number of receptors/enzymes proteins (e.g., estrogen receptor, androgen receptor, HIV protease) compared to non-carborane ligands. [5][6][7][8][9][10][11] Despite the utilization of closo-carboranes as hydrophobic scaffolds in drug design and as boron-delivery moieties for BNCT has expanded, in silico molecular modeling of carborane-containing molecules with macromolecules including docking studies, scoring functions and virtual screening have been rarely reported.…”
Section: 4mentioning
confidence: 99%